South Korea and North Korea: Differences in Ideology and Their Impact on War - Daniela, Nurfaizah Azhari; Soemantri, Asep Iwa (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This article analyzes the ideological differences between South Korea and North Korea and their impact on war, especially the Korean War (1950-1953). South Korea adheres to the ideology of liberal democracy and capitalism, while North Korea practices the ideology of Juche, socialism and autonomy. These differences have deepened conflict on the Korean Peninsula, reaching its peak in the Korean War. The impact is felt to this day with military tensions in the DMZ. Despite this, reconciliation efforts have been made, offering hope for peace in the region. This research was conducted descriptively using a literature study which was then analyzed to identify ideological differences between South Korea and North Korea and their impact on the war.